2022
DOI: 10.3389/fmicb.2022.909274
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nontuberculous Mycobacteria Species on Mortality in Patients With Nontuberculous Mycobacterial Lung Disease

Abstract: Patients with nontuberculous mycobacterial lung disease (NTM-LD) have increased mortality. The impact of NTM species on the risk of mortality remains unclear, especially that of death by non-cancer causes. We conducted a retrospective cohort study from 2006 to 2018 in a tertiary-care hospital in Taiwan. We enrolled patients who fulfilled the microbiological diagnostic criteria of NTM-LD. The mortality causes within 8 years after diagnosis were identified, and the Cox proportional hazard regression was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…More than 190 non-tuberculous mycobacteria (NTM) species have been identified and the incidence is increasing globally, ranging from 15.2/100 000 to 41.3/100 000 (USA and Canada) 1 2. The mortality is high (35.3%),3 and the morbidity is significant 4. The microbiological cure rate is as low as 45% 5…”
Section: Introductionmentioning
confidence: 99%
“…More than 190 non-tuberculous mycobacteria (NTM) species have been identified and the incidence is increasing globally, ranging from 15.2/100 000 to 41.3/100 000 (USA and Canada) 1 2. The mortality is high (35.3%),3 and the morbidity is significant 4. The microbiological cure rate is as low as 45% 5…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of NTM diseases is increasing worldwide (Kendall & Winthrop, 2013); for example, in the United States, the prevalence of NTM diseases has been rising from 8.2 per 100,000 persons in 1994 to 16 per 100,000 persons in 2014 (Donohue, 2018). Moreover, recently, Wang et al (2022) reported that patients with NTM lung disease in Taiwan have increased mortality. While it has long been known that aquatic environments are a source of NTM that can infect people and animals, there is still insufficient knowledge of the ecology and sources of human exposure to many NTM species (Pavlik et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Nontuberculous mycobacterial (NTM) infection has become an emerging crisis worldwide due to its rising mortality rates of up to 45% [1][2][3]. In most countries, M. abscessus complex (MABC) is one of the predominant NTM species in Taiwan, secondary to Mycobacterium avium complex [4,5].…”
Section: Introductionmentioning
confidence: 99%